BRAND REGISTRATION’S ASSISTANCE “PT. FLUORITE M EDIA INDONESIA” IN GETTING LEGAL PROTECTION - Revlina Salsabila Roselvia; Yudi Kornelis (ConCEPt - Conference on Community Engagement Project, 2022)
This internship program aims to help the community. This program is a form of Community Service (PKM) in the form of assistance in trademark registration. PT. Fluorite Media Indonesia is a business engaged in photography and providing photo studio services. This business was founded in 2018. In opening a business in which there are competitors - other business competitors who have high competitiveness, legal protection there is a brand that is very necessary in protecting the brand so that there is no violation or imitation of unscrupulous irresponsible. Legal protection related to trademarks is regulated in Law No. 15 of 2001. The purpose of this trademark protection registration is to prevent plagiarism of the business mark. The data collection method in this Community Service (PKM) activity uses partner data collection methods, location information, details of trademark registration fees with trademark rights registration